2018 International Conference on Frontiers of Information Technology (FIT) 2018
DOI: 10.1109/fit.2018.00036
|View full text |Cite
|
Sign up to set email alerts
|

From Traditional to Technologically Influenced Audit: A Compliance Perspective

Abstract: Business monitoring is characterized as multidisciplinary, which has its roots in service sciences and accounting. A major challenge in this area of research is to bridge the gap from two distant worlds of service science and accounting. Smart auditing framework proposed an initial solution to bridge the gap. In this paper, background knowledge for basic and related concepts to understand the relationship of compliance and Service Oriented Architecture (SOA) has been established. Basic concepts behind these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Auditors who enhance professionalism and possess sufficient expertise in their professional field contribute to an increase in quality performance [14]. It has also been found that the most popular classification of audits is based on their execution, namely internal and external audits [15]. Numerous factors can influence the performance of auditing, as indicated by research suggesting that audit experience has a linear impact on auditing performance.…”
Section: Figure 1 Computerized Methods Influencing Auditor Performanc...mentioning
confidence: 99%
“…Auditors who enhance professionalism and possess sufficient expertise in their professional field contribute to an increase in quality performance [14]. It has also been found that the most popular classification of audits is based on their execution, namely internal and external audits [15]. Numerous factors can influence the performance of auditing, as indicated by research suggesting that audit experience has a linear impact on auditing performance.…”
Section: Figure 1 Computerized Methods Influencing Auditor Performanc...mentioning
confidence: 99%
“…As compliance becomes a major issue, the effect of optimization is thought of as a strategic concern, such that business compliance requirements can be achieved by applying smart audit techniques that can only come from IT knowledge [86].…”
Section: Business Process Compliancementioning
confidence: 99%